ANALISIS KEMAMPUAN KONEKSI MATEMATIS SISWA SMP DALAM MENYELESAIKAN SOAL CERITA STATISTIKA DITINJAU DARI SELF-CONCEPT - Elanda Maharani Putri, Era; Marhadi Saputro; Yudi Darma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to describe students' mathematical connection ability in solving story problems in terms of self-concept. This research is a qualitative descriptive method. The form of this research is a case study. This research was conducted at SMP Negeri 1 Marau. The subjects of this research are students of class VIII C who have studied statistics material. The subjects to be interviewed consisted of 6 students based on high, medium, and low self-concept categories. The subjects of this study were determined using purposive sampling technique. The purposive sampling technique is sampling using certain considerations in accordance with the desired criteria. The instruments used in this research are questionnaires, written tests and interview guidelines. The results showed that students with high category self-concept were able to fulfill all indicators of mathematical connection ability, namely understanding relationships between topics, finding equivalent representations of the same concepts and procedures, and using mathematics in other fields of study or everyday life. This is because students with high self-concept are always optimistic and do not give up easily in solving the problems they face. Students with moderate self-concept category are able to fulfill 2 indicators from 3 indicators of mathematical connection ability, namely finding equivalent representations of the same concepts and procedures, and using mathematics in other fields of study or everyday life. While students with low self-concept are able to fulfill 1 indicator from 3 indicators of mathematical connection ability, namely using mathematics in other fields of study or everyday life. This is because students with low self-concept also tend to hesitate and give up easily in dealing with the problems they face.